نقاط الالتقاء بين القواعد التحويلية والقواعد العربية وتطبيقها في النصوص العربية - Nurul Fatihah Hanapi (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2013)
This study aims to determine a meeting point between transformational grammar rules with the Arabic grammar through the analysis of Arabic texts including the Quran, hadith and Arabic poetry. Since there are many different opinions and views on the authenticity of Arabic grammar, its development and elements in the Arabic grammar method, this has resulted in the researcher taking the initiativeto conduct the current study by reviewing existing methods of transformational grammar in Chomsky's linguistic theory which was developed in ١٩٥٧. The existence of"tabῑattal-lughat" which is one of the elements in Chomsky's theory might be able to answer these opinions. In addition, it aims to seek the impact of transformational grammar rules on the rules ofArabic language such as in Sibawayh, Jurjᾶni and many others. In addition,it intends to reveal the drive of Chomsky's transformational theory as well as to find the meeting point between Chomsky and Arabic grammar. This study employs a comparative method to analyze Arabic and English texts. The results of this study have enabled there searcher to explain the important aspects in Chomsky's linguistic theory such as the "creative aspect" of the brain in which according to Chomsky,is the nature of human beings.